2020 25th International Conference on Pattern Recognition (ICPR) 2021
DOI: 10.1109/icpr48806.2021.9412923
|View full text |Cite
|
Sign up to set email alerts
|

Total Estimation from RGB Video: On-line Camera Self-Calibration, Non-Rigid Shape and Motion

Abstract: In this paper we present a sequential approach to jointly retrieve camera auto-calibration, camera pose and the 3D reconstruction of a non-rigid object from an uncalibrated RGB image sequence, without assuming any prior information about the shape structure, nor the need for a calibration pattern, nor the use of training data at all. To this end, we propose a Bayesian filtering approach based on a sum-of-Gaussians filter composed of a bank of extended Kalman filters (EKF). For every EKF, we make use of dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…For example, Faugeras et al (1992) demonstrated camera self-calibration without a pattern, based on which Qian and Chellappa (2004) and Civera et al (2009) proposed to use sum of Gaussian filters. Recently, Agudo (2021) extended the above works to use RGB video with objects of non-rigid shape for camera self-calibration.…”
Section: Camera Calibrationmentioning
confidence: 99%
“…For example, Faugeras et al (1992) demonstrated camera self-calibration without a pattern, based on which Qian and Chellappa (2004) and Civera et al (2009) proposed to use sum of Gaussian filters. Recently, Agudo (2021) extended the above works to use RGB video with objects of non-rigid shape for camera self-calibration.…”
Section: Camera Calibrationmentioning
confidence: 99%
“…To ensure the various capabilities of a mobile robot, visual simultaneous localization and mapping (VSLAM) are considered fundamental issues. In recent decades, VSLAM systems [1][2][3][4][5][6][7] based on visual sensors have attracted increasing attention and been well studied, with a rather satisfactory performance that can facilitate high-level tasks [8][9][10]. Typically, some well-performing VSLAM systems have been developed, such as ORB-SLAM2 [3] and LSD-SLAM [2].…”
Section: Introductionmentioning
confidence: 99%